Experiences of Veteran and Civilian Patients in Exploratory Yoga Sessions for Chronic Pain: A Qualitative Study - Amy Huang; Jennifer Anthonypillai; Eleni G. Hapidou (Taylor & Francis Group, 2023)
ABSTRACTBackground Yoga integrates all aspects of self, with biological, mental, intellectual, and spiritual elements. The practice of yoga aligns with the biopsychosocial model of health and, as such, it can be instrumental in pain treatment.Aims The purpose of this qualitative study was to explore perceptions regarding the yoga sessions for chronic pain through thematic content analysis with comparison of gender, veteran or civilian status, and delivery methods.Methods Patients with chronic pain attended a 5-week intensive interdisciplinary chronic pain management program at the Michael G. DeGroote Pain Clinic. Participants were asked to complete six open-ended questions following four weekly 1-h yoga classes, through in-person or virtual delivery. Survey responses were thematically and separately analyzed by reviewers.Results Forty-one (N = 41) participants (56% males, 71% veterans) with an average age of 50.87 (SD 10.10) years provided comments. Nine themes emerged: (1) mind and body are one through yoga practices; (2) meaningful practice of yoga basics is productive for range of motion/movement, tension in joints, and chronic pain; (3) yoga classes provide an enjoyable process of learning; (4) yoga reminds patients of their physical capabilities; (5) routine practices lead to improvements; (6) yoga improved on strategies for chronic pain; (7) yoga can be adapted for each patient; (8) mindset improves to include positive thinking, better focus, and willingness to try new things; and (9) improvements exist for the current yoga programming.Conclusion Findings of the current study were nine qualitative themes that present the experience of patients with chronic pain in the yoga sessions.